On the Use of Inertial Sensors in Educational Engagement Activities. (2015) - Espinosa, Hugo G.; Lee, Jim; Keogh, Justin; Grigg, Josie; James, Daniel A.
Abstract: Wearable sensors have been successfully used for a few decades in different sporting applications and its use has been constrained mostly to research projects. However, its positive impact has been recently adding other directions towards education, commercial and servicing. The establishment of Sports Engineering as a discipline is playing an important role in Australian universities where relevant material and emerging technologies are required to be taught and in certain circumstances developed. Some of these technologies include the adoption of inertial sensors (accelerometers and gyroscopes). This paper shares the impact of inertial sensors in building engagement in different educational activities at secondary level, with the purpose of engaging them into Sports Engineering disciplines, and at tertiary level through teaching undergraduate and post-graduate programs.